Effect of Holes In The Femoral STEM Made of Ti6AI4V On The Strength of The Material - Wulandari, Diah (Proceeding Series of International Conference on Arts and Humanities, 2022)
Osteoarthritis (OA) is a joint disease due to a chronic inflammatory process in the joints and bones around the joints which is degenerative. The body parts that often experience osteoarthritis are the hands, knees, hips, and spine. Hip osteoarthritis (hip osteoarthritis) occurs in the hip joint (ball-and-socket joint) with the femoral head. One of the medical efforts made by orthopedic doctors to treat hip osteoarthritis is to replace the implant material in the hip joint called a hip prosthesis. Currently, Indonesia is still importing Hip Prosthesis to meet national needs. However, what we know is that the anatomy of the Indonesian people (Mongoloid race) is different from the anatomy of other races in the world. Apart from the size, the price of imported implants will be much more expensive than those produced domestically. This study focused on modeling the femoral stem with titanium Ti6AI4V through SOLIDWORK and then simulating it using ANSYS software. The variables analyzed included stem length, offset length, and the magnitude of the force received by the implant for several activities such as normal walking, climbing and descending stairs, and tripping. The femoral stems analyzed were the smallest size femoral stem (size 3) with a length of 129 mm and a medial offset of 39.1 mm and the largest size femoral stem (size 11) with a length of 161 mm and a medial offset of 46.7 mm. The entire stem has a centrum-collum diaphysis angle (CCD) of 134 degrees. The patient’s body weight was 700 N. The simulation results of the stress analysis showed that the design of the femoral stem size 11 was better than the other femoral stems in terms of stress distribution. The greatest stress that appears due to tripping causes the maximum von Mises stress on the femoral stem of 2487, 6 MPa and 5243, 4 MPa for size 11.